Impact and consequences of sexual offences in the metaverse using the example of virtual rape - Steffes, Bianca (Deviant behavior, 2025)
The metaverse is an online environment in which people, represented by their avatars, can interact in virtual spaces. Harmful activities may occur as avatars interact. In particular, sexual crimes might be a serious problem in the metaverse. In this interdisciplinary article, we discuss virtual rape in the metaverse. To this end, we provide a legal analysis of the relevant issues, exemplified by German criminal law, and discuss whether a sexual offense can be committed without physical contact. The legal issues are flanked by a psychological assessment of how various factors of the metaverse can influence the psychological and physical perceptions of users. In a final step, we address technical measures that might be appropriate to protect users from sexual assault based on legal and psychological considerations.